PENGARUH PENGKAYAAN ARTEMIA OLEH BEBERAPA SUMBER MINYAK TERHADAP PERTUMBUHAN LARVA KERAPU TIKUS (Cromileptes altivelis) - Resmayeti Purba (University of PGRI Palembang, 2004)
A research on Artemia naupli enrichment of Grace Kelly grouper, Cromileptes altivelis was conducted in order to investigasi its effects on the growth, which was reflected by the relative growth of total length amd of weight, respectively. Three different enrichments treatments i.e fish oil, corn oil and coconut oil were fed on larva for 40 days. Initial total length of the larva was about 2.010 ± 0.2559 cm. The larva feed on Artemia naupli at density of 2-5 ind/ml. The result indicated that Artemia naupli enriched fish oil 0.1 g/100 ml water en able to of brain volume, relative growth of total length and relative growth of weight better (p<0.05). The brain volume, relative growth of total length and relative growth of weight larva fed Artemia naupli enriched with fish oil was x 103 µm3, 60,97% and 372,40% larva fed Artemia naupli enriched with corn oil was 1.21x 103 µm3, 52,09% and 225.80% and fed Artemia naupli enriched with coconut oil was 1.29 x 103 µm3, 50.97% and 200.10%Keywords: Artemia, enrichment, fish oil, growth larva